KAJIAN KUALITAS MINYAK GORENG SAWIT DENGAN METODE TAGUCHI QUALITY LOSS FUNCTION - Juliza Hidayati; Sukaria Sinulingga; Utomo Hadi (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. A company making palm olein find the results of the productionprocess has some variation of the characteristics of the oil, which is a variation ofcolors, smells, acid number and moisture content. Variations occur due to theheating temperature in the engine Slurry Tank, spiral heat exchange machines anddeodorize machine that changed the conditions required. This resulted in financiallosses for the company. The research was conducted by examining thecharacteristics of the oil, which aims to get real-time comparison of thecharacteristics and expectations of the value characteristics of color, odor, acidnumber and moisture content. Furthermore, the interviews and the cost of losscalculation using the Taguchi Quality Loss Function to improve the characteristicsof the product which is not according to specifications. Research shows loss costper color characteristics of 0.099%, the characteristic odor of 0.077%, thecharacteristics of acid number of 0.1% and the characteristics of the water contentof 0.0002%. While the total cost of loss to Rp 269 319 600 / year. If doneimprovement of production processes, then the resulting cost reductionsamounting to 18.65% or USD 50.2524 million / year. The losses reached 18.65%showed losses during the company is quite large, so it is necessary improvementof the production process to minimize lost production costs.Keywords: Cooking Palm Oil, Taguchi Quality Loss Function, ProductCharacteristics, Production Cost